Assessment of choice of Pre-Wedding and Honeymoon Destination Selection from the Perspectives of Asian couples - Kanthita Thephee (Prince of Songkla University, 2021)
Thesis (M.B.A., Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2018